فعالية استخدام كتاب الصرف للمستوى الثاني من سلسلة تعليم اللغة العربية لتنمية مهارة القراءة لدى طالب الفصل الثاني العالية بمعهد نور الإسلام غنتي لمبوك الوسطى - Josman, Yosal; Ardiani, Ika Tri (Universitas Negeri Semarang, 2021)
لقد قام الباحث بمشاهدة وملاحظة تطبيق وتعليم اللغة العربية في فصل الثاني العالية بمعهد نور الاسلام غنتي فوجد الباحث بعض المشكلات اللغوية خصوصا في مهارة القراءة، منها عدم الممارسة على قراءة الجهرية، القراءة المتقطعة، القفز عن بعض الكلمات، التكرار في القراءة، عدم معرفة قواعد الصرفية. ووجد الباحث بعض المشكلات النفسية منها إهمال المعلم، القراءة بلا رغبة والاهتمام. والأسس المشكلات المذكورة في السابقة هو المشكلات التعليمية يعني الكتاب المستخدم في هذا المعهد ليس الكتاب التعليمي. بناءا على هذه المشكلات قام الباحث بالبحث الذي يهدف إلى معرفة مدى فعالية استخدام كتاب الصرف للمستوى الثاني من سلسلة تعليم اللغة العربية لتنمية مهارة القراءة لدى طلاب الفصل الثاني العالية بمعهد نورالاسلام غنتي ولمعرفة طريقة تعليم سلسلة تعليم اللغة العرابية وفضل الباحث منهجية الكمي، لأن الباحث استخدم نوع البحث التجريبي. وبعد القيام بالتجربة وتحليل البيانات حصل الباحث على خلاصة وهي أن استخدام كتاب الصرف للمستوى الثاني من سلسلة تعليم اللغة العربية لتنمية مهارة القراءة فعال. اعتمادا على النتائج التي حصل عليها الطلاب في الاختبار القبلي والبعدي. معدل نتائج الطلاب في الاخبار القبلي هي 52,50 وتكون الاختبار البعدي هي 90,00 تدل على أن نتائخ الطلاب ترتفع ارتفاعا شديدا بعد التجربة باستخدام كتاب الصرف للمستوى الثاني من سلسلة تعليم اللغة العربية. وهذا موثوق بنتيجة المقابلة. The researcher saw and observed the application and teaching of the Arabic language in the second semester of the high school at the Nurul Islam Ganti Institute, and the researcher found some linguistic problems, especially in the skill of reading, including lack of practice in reading aloud, intermittent reading, skipping some words, repetition in reading, lack of knowledge of morphological rules. The researcher found some psychological problems, including neglect of the teacher, reading without desire and attention. The foundations of the problems mentioned in the previous one are educational problems, meaning the book used in this institute is not the educational book. Based on these problems, the researcher conducted research aimed at knowing the effectiveness of using the textbook for the second level of the Arabic language education series to develop the reading skill of the second semester high students of the Nurul Islam Ganti Institute and to know the method of teaching the Arabic language teaching series and the researcher preferred the quantitative method, because the researcher used the type empirical research. After doing the experiment and analyzing the data, the researcher got a conclusion, which is that using the exchange book for the second level of the Arabic language teaching series to develop reading skill is effective. Depending on the results obtained by students in the pretest and the post-test. The average results of the students in the tribal news is 52.50 and the post test is 90.00 indicating that the students ’results rise dramatically after the experiment using the exchange book for the second level of the Arabic language teaching series. This is reliable with the outcome of the interview.